Coastal Carolina cooking - Davis, Nancy, 1960-; Hart, Kathy, 1957- (University of North Carolina Press, 1986)
For generations, coastal North Carolinians have prepared and savored time-honored recipes that are as much a part of their tradition as boatbuilding and net making. Home-cooked meals using the great variety of seasonal foods remain central to family life. In this collection, Nancy Davis and Kathy Hart have preserved an important part of the heritage of this region. Here 34 Tar Heel cooks offer recipes that can't be found in popular cookbooks or on restaurant menus. In Edenton, Frances Drane Inglis shares her recipe for plum pudding from the pages of a 19th-century family cookbook. And from Gloucester, Bill Pigott offers one of his specialties, conch chowder, a Carteret County classic. These cooks describe more than just good food; they recount the heritage of the coast through stories, anecdotes, helpful tips and historical facts. Vignettes on each cook lend a historical perspective to this book and the old-time recipes will be treasured for years to come.